Report of a rare case of hand-foot-mouth disease in a adult woman with systemic arthritis - Nóbrega, Luciana Eloísa da Silva Castro; de Oliveira, Viviane Alves; de Oliveira, Patrícia Teixeira; da Silveira, Éricka Janine Dantas; de Medeiros, Ana Myriam Costa (Brazilian Dental Science, 2016)
Hand-foot-mouth disease (HFMD) is a highly infectious disease, rare in adults which usually presents a painfull stomatitis. We describe a rare case of HFMD in a 34-year-old woman with medical history of recent intestinal infection and systemic arthritis with only oral and hands involvement. Additionally, we discuss diagnosis and treatment of this disease and reinforce the importance of the correct diagnosis because delayed diagnosis can cause spread of the disease. Keywords: Adult; Arthritis; Mouth diseases.